The Socio-Economic Impact of Waste Incinerator Technology Implementation on Scavengers’ Livelihoods in Malang City - Deni Nugroho Setyabudi; Francisco Marcel; Alexander Herlambang (Bulletin of Management and Business, 2025)
The application of incinerator technology in urban waste management has become one of the modern solutions to reduce waste volume and generate alternative energy. However, in the city of Malang, the implementation of incinerator technology remains limited due to social and economic consequences for community groups that have long depended on waste collection and sales activities, particularly scavengers. This study aims to analyze the social and economic impacts of implementing incinerator technology on the livelihoods of scavengers in urban areas of Malang. The research employs a descriptive qualitative approach through interviews, field observations, and discussions with local government authorities. The results indicate that the presence of incinerators has positive social impacts, such as the emergence of new job opportunities in supporting activities — including the collection of high-value inorganic waste and employment around incinerator facilities. However, there are also negative economic impacts, particularly a decline in scavengers’ income, especially among those who rely on recycling as their main source of livelihood, due to the reduced volume of recyclable waste. These findings suggest that the implementation of incinerator technology requires inclusive policies that consider the economic sustainability of vulnerable groups such as scavengers, through skill training programs, integration into the formal waste management system, or recycling-based economic empowerment initiatives.